Addressing Poverty and Gender Inequality through Access to Formal Credit and Enhanced Enterprise Performance in Nigeria: An Empirical Investigation. (February 2017) - Nwosu, Emmanuel O.; Orji, Anthony
Abstract: Addressing poverty and gender inequality is one of the fundamental targets of the sustainable development goals. Access to finance, however, has been identified as one of the ways to reduce poverty and gender inequality. The main focus of this study, therefore, is to ascertain the impact of access to formal credit on enterprise performance. The study uses Nigerian Enterprise Surveys data for 2010 to construct a direct measure of credit constraint. From propensity score estimations, the results show that access to formal credit matters and has significant impact on enterprise performance indicators. Firms that are credit constrained have significantly lower output per worker, capital per worker, employment of labour and investment in fixed assets for expansion compared to firms that are not credit constrained. This is more pronounced for women‐owned enterprises after adjusting for bias in the estimations and controlling for sampling weights. This suggests that one way to support the growth of enterprises in Nigeria is to make access to formal credit less stringent. Also, government and monetary authorities should support credit expansion policies for medium and small enterprises in Nigeria.